Kesepian dengan Nomophobia Pada Mahasiswa - Andrea Christine Santoso; Christiana Hari Soetjiningsih (Bulletin of Counseling and Psychotherapy, 2022)
This research is quantitative research that aims to acknowledge the relationship between loneliness and nomophobia for Psychology students from Satya Wacana Christian University. The population in this research are both male and female students from batch 2018 to 2021. The participants were taken randomly, a total of 76 participants. The researcher applieds incidental sampling in taking the sample for this research. There are two measurement tools in this research. The first measurement tool is UCLA Loneliness Scale Version 3, which was developed by Rusell and the second is Nomophobia Questionnaire (NMP-Q) scale which was developed by Yildrim and Correia. Based on the result of the analysis using the product-moment Pearson correlation, it was found that there is a significantly positive relationship between loneliness and nomophobia for students of the Psychology study program from Satya Wacana Christian University. It can be inferred that a higher loneliness level leads to a higher chance of nomophobia, and vice versa, lower loneliness leads to a lower chance of nomophobia. The result of this research can be used as a reference in trying to decrease loneliness and increase the effectiveness of smartphone usage to avoid nomophobia.